Variability of enterprise architecture elements in Finnish ePrescription projects - Hannu Virkanen; Juha Mykkänen; Mika Tuomainen (Finnish Social and Health Informatics Association, 2014)
The governance of large eHealth initiatives is complicated by multiple viewpoints and autonomy of numerous different stakeholder organizations. In addition, the lifecycle of goals and requirements spans multiple different organizations, as well as various specification, development and deployment projects, application systems and products. Governance requires traceability of requirements and design decisions in the lifecycle of large-scale initiatives and between various levels of abstraction. Enterprise architecture (EA) approaches have been used for governance of complex and long-term intra- and inter-enterprise initiatives. We provide a model which we use to conceptually analyze variability of several EA elements throughout the extended lifecycle of development goals of projects related to national ePrescription in Finland. The analysis is based on case experience, material and interpretive methods in relation to nine projects. The analyzed elements and EA artefacts have been proposed as being especially central and relevant for many enterprise architecture initiatives. The results illustrate the differences in presence, plurality and abstraction level of central EA elements throughout the project continuum of ePrescription. The results highlight dependencies and transformations which are likely to be encountered in large-scale eHealth efforts in general. The results may be used to support the traceability and refinement of EA elements in the planning and governance of interdependent projects.